2018
DOI: 10.1186/s12883-018-1173-6
|View full text |Cite
|
Sign up to set email alerts
|

The management of common recurrent headaches by chiropractors: a descriptive analysis of a nationally representative survey

Abstract: BackgroundHeadache management is common within chiropractic clinical settings; however, little is yet known about how this provider group manage headache sufferers. The aim of this study is to report on the prevalence of headache patients found within routine chiropractic practice and to assess how chiropractors approach key aspects of headache management applicable to primary care settings.MethodsA 31-item cross-sectional survey was distributed to a national sample of chiropractors (n = 1050) to report on pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Overall estimates suggest that final-year students have a slightly higher self-perceived preparedness and a slightly higher proficiency in headache diagnosis and management compared to those students in the 4th year of study. Since headache patient caseload is substantial within Australian chiropractic clinical practice, 12,24 it is important to better understand graduate student confidence and proficiency in headache patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall estimates suggest that final-year students have a slightly higher self-perceived preparedness and a slightly higher proficiency in headache diagnosis and management compared to those students in the 4th year of study. Since headache patient caseload is substantial within Australian chiropractic clinical practice, 12,24 it is important to better understand graduate student confidence and proficiency in headache patient care.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Internationally, headache disorders rank in the top 5 conditions for which people seek help from chiropractors, 11 and 1 in 5 new patients seeking help from Australian chiropractors are reported to have a chief complaint of headache. 12 Accordingly, it is vital that chiropractic students learn to generate a headache diagnoses following internationally recognized classification of criteria 7 and learn to develop a management care plan for those with headaches following an evidence-based rationale. 8 Previous international studies have identified that chiropractic graduate students can perceive themselves to be unprepared within certain clinical competencies, raising concerns about gaps that may exist between student education and practice-ready practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…These chiropractors include a belief that the use of ICHD primary headache criteria influences their patient management. Previous studies have reported the use of manual therapies, exercise therapies and advice on headache triggers as common to chiropractic headache management [30, 54]. While advice on headache triggers is well recognised as an important aspect of primary headache management [55, 56], the effectiveness of manual and exercise therapies for the prevention of primary headaches requires further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding from our results was that chiropractors engaged in primary headache diagnosis are less likely to undertake patient referral to assist with headache prevention. A recent Australian study showed chiropractors refer headache patients to both complementary health care providers (including acupuncturist, herbalist, naturopath, massage therapist, counsellor) and general practitioners [30]. For tension headache, preventative treatment guidelines advise non-drug management first be considered [64] and provide recommendations for behavioural treatments such as electromyography (EMG) biofeedback (level A), cognitive-behavioral therapy and relaxation training (level C), massage therapy (level C) and acupuncture (level C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation